Child-friendly Schools: Implementation of Ethnoscience-based Science Learning - Dewi, Kustiyanti; Wasino, Wasino; Sawri, Sarwi; Witasari, Nina (Universitas Negeri Semarang, 2024)
This research aims to explore and analyze the implementation of ethnoscience-based Natural and Social Sciences (IPAS) learning in child-friendly schools. An ethnoscience approach that integrates local knowledge, and wisdom aims to create a learning environment that is relevant, inclusive, and supports students' holistic development. The research method used is a descriptive qualitative approach. The subjects of this research were teachers and students at an elementary school at SDN 01 Jatibarang Mijen, Semarang City which implemented the child-friendly school concept. Data was collected through observations, interviews and document analysis. Observations were carried out to see the learning process in the classroom, while in-depth interviews with teachers and students aimed to understand their perceptions and experiences of ethnoscience-based science and science learning. Document analysis includes curriculum, learning implementation plans (RPP), and teaching materials. The results of the research show that the implementation of ethnoscience-based science and science learning in child- friendly schools succeeded in creating a fun, inclusive and interactive learning atmosphere resulting in an increase in understanding of science and science concepts and appreciation for local culture. In conclusion, ethnoscience-based science and science learning in child-friendly schools is not only effective in improving the quality of learning, but also in building a learning environment that respects children's rights and local culture. The recommendation from this research is the further development of teacher training programs and the provision of learning resources that support the implementation of ethnoscience in child- friendly schools to achieve inclusive and meaningful education.